E17K substitution in AKT1 in prostate cancer - Boormans, J L (Nature Publishing Group, 2010)
BACKGROUND: The phosphatidylinositol 3-kinase (PI3K)–AKT pathway is activated in many cancers. Mutational hotspots in AKT1 and in the regulatory and catalytic subunits of PI3K have been detected in multiple tumour types. In AKT1, the E17K substitution leads to a PI3K-independent activation of AKT1. METHODS: A mutational profiling of AKT1 and of the mutational hotspots in PIK3CA and PIK3R1 was carried out in samples from primary and recurrent prostate tumours. RESULTS: We show that, in prostate cancer, AKT1(E17K) had a prevalence of 1.4%. The mutation seemed to be associated with a favourable clinical course but it was not associated with a specific tumour growth pattern. Activating mutations in PIK3CA or PIK3R1 were not found in prostate cancer. CONCLUSION: The E17K substitution in AKT1 is rare in prostate cancer. It seems associated with a favourable clinical outcome but not with a specific histology of the tumour.